Transaction Cost Economics: An Introduction - Oliver E. Williamson (Kiel Institute for the World Economy (IfW), 2007)
This overview of transaction cost economics is organized around the "Carnegie Triple" - be disciplined; be interdisciplinary; have an active mind. The first of these urges those who would open up the black box of economic organization to do so in a modest, slow, molecular, definitive way, with the object of deriving refutable implications and submitting these to empirical testing. The second recommends that the student of economic organization be prepared to cross disciplinary boundaries if and as this is needed to preserve veridical contact with the phenomena. The injunction have an active mind is implemented by being curious and asking the question "What is going on here?" The paper concludes with a discussion of operationalization.
Keywords: D2; D73; D86; L2; 330